GE_GERICHTE A/1360/2006 vom 26. November 2007 - GE Cour de justice (2007)
; AI(ASSURANCE) ; EXPERTISE PSYCHIATRIQUE ; EXPERTISE MÉDICALE ; ALCOOLISME ; DÉPENDANCE(MALADIE) ; FORCE PROBANTE | LPGA8; LAI4